Dark water rising - Hale, Marian (New York : Henry Holt and Co., 2006)
While salvaging and rebuilding in the aftermath of the Galveston flood of 1900, sixteen-year-old Seth proves himself in a way that his previous efforts never could, but he still must face his father man-to-man.
HornBook Gde
BCCB
Booklist
Sch Libr Jnl
10 + up.
10-14.
Keywords: Hurricanes -- Texas -- Galveston -- Juvenile fiction